On-the-fly diagnosability analysis of bounded and unbounded labeled Petri nets using verifier nets - Li, Ben; Khlif-Bouassida, Manel; Toguéyni, Armand (Zielona Góra: Uniwersytet Zielonogórski)
This paper considers the problem of diagnosability analysis of discrete event systems modeled by labeled Petri nets (LPNs). We assume that the LPN can be bounded or "unbounded" with no deadlock after firing any fault transition. Our approach is novel and presents the on-the-fly diagnosability analysis using verifier nets. For a given LPN model, the verifier net and its reachability graph (for a "bounded" LPN) or coverability graph (for an "unbounded" LPN) are built on-the-fly and in parallel for diagnosability analysis. As soon as a diagnosability decision is established, the construction is stopped.
Keywords: fault diagnosis; discrete event systems; labeled Petri nets; on-the-fly diagnosability analysis; verifier nets